Animal waqf as a thrust of social entrepreneurship - Mar Iman, Abdul Hamid; Mohammad, Mohammad Tahir Sabit (2020)
This paper is a foundation study on the concept of animal unit waqf (AUW). It is the first of its kind, based on local circumstances where there exists a need to encourage small farmers’ participation in animal husbandry in poverty-stricken and lack-of employment states in Malaysia, through the concept of waqf. Understandably, poor members of the community who wish to raise animals as a source of living do not find an affordable means of beginning a herd. Livestock waqf could be offered as an approach to resolving this issue. Based on the concept of social entrepreneurship, this paper explores the mechanism of livestock waqf, in particular the bahīmatul an’ām, that could be introduced to the farming community in Malaysia.